ANALISIS SPASIAL KEPADATAN VEKTOR DENGAN ANGKA KEJADIAN DEMAM BERDARAH DENGUE DI KECAMATAN MALALAYANG KOTA MANADO - Joy V.I. Sambuaga; Yozua T. Kawatu; Steven Jacub Soenjono (Jurnal Kesehatan Lingkungan, 2013)
Dengue Haemorrhagic Fever(DHF) to be one ofthe moreserioushealthprobleminIndonesiaandoften createsanExtraordinary Incident(KLB). The disease isa public health probleminIndonesiabecause ofits highprevalenceandspreadmore widely. Untilnow there is noeffective vaccinetopreventdengueinfection.The study wasobservationalanalytic, with across-sectionalstudy design. The purposeof this studywas tomap thedensity ofthe vectorfordengue fever(House Index, Container Index,BreteauIndex), tomap the spreadof dengue casesandto analyzethe influence ofthe vectordensityDBD(House Index, Container Index,Indexand FiguresBreteauFreeFlick) on the incidencedenguein the districtMalalayangManado. Samples were takenateach housecasesrecordedeveryneighborhoodin the VillageMalalayangIpresentthe case ofDBDandretrievedthe coordinates, the following 15 housesthat surroundthecases(15cases ofthis houseincluding the case house) using GPS. The results showedthere is astrong relationship betweenthe density oflarvaewith the incidenceof dengue casesin the VillageMalalayangI andthe density ofdenguevectorsanddengue casescanspasial